Katekese Umat Kontekstual: Sebuah Upaya Penyembuhan Luka Batin untuk Meningkatkan Ketenteraman Umat - Gregorius Daru Wijoyoko; Ambrosius Heri Krismawanto; Santoso (Jurnal Penelitian Pendidikan Agama Katolik, 2024)
The utilization of retreats for emotional healing is a form of catechesis that can aid in the spiritual development of Christians. Traditional catechesis methods, such as lectures and deepening of faith, have not yielded the desired outcomes in the Semarang Archdiocese region. These methods primarily focus on cognitive and kerygmatic aspects, neglecting to effectively address emotional and behavioral achievements in Diakonia, koinonia, and inter-faith dialogue. This research aims to develop a model of catechesis utilizing the retreat method for emotional healing and to identify the factors contributing to its success or failure. The Research and Development method is utilized in this study, with the analysis of 100 subjects. The findings suggest that in order to optimize the implementation of Christian values, there must be improvements in both the internal quality (such as closeness to God, willingness to participate in retreats for emotional healing, deepening of theological knowledge, emotional intelligence, effective communication skills, and self-control) and external quality (the closeness of the retreat participant's relationship with God and the readiness of the student to learn) of catechists.